2016
DOI: 10.1002/chem.201504242
|View full text |Cite
|
Sign up to set email alerts
|

Stable Crystalline Forms of Na Polysulfides: Experiment versus Ab Initio Computational Prediction

Abstract: For the design of light-metal-sulfur batteries and for the understanding of their performance, knowledge on the stable crystalline polysulfides is very important. We confronted experimental and ab initio crystal structure prediction studies on the stability of Na polysulfides. The selected evolutionary-based structure-prediction algorithm was able to quickly and correctly predict the thermodynamically stable crystalline forms of Na polysulfides with small unit cells. For Na polysulfides with large unit cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…To search all potential stable ground‐state structures of the Mg–Ge system, an ab initio variable‐composition evolutionary method USPEX was performed at 50, 100, 150, and 200 GPa . Its success was demonstrated by determining the stable structures of the various compounds . All structural optimizations, calculations of the enthalpies, electronic calculations, and other structural property calculations were performed with the Vienna ab initio simulation package (VASP) .…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…To search all potential stable ground‐state structures of the Mg–Ge system, an ab initio variable‐composition evolutionary method USPEX was performed at 50, 100, 150, and 200 GPa . Its success was demonstrated by determining the stable structures of the various compounds . All structural optimizations, calculations of the enthalpies, electronic calculations, and other structural property calculations were performed with the Vienna ab initio simulation package (VASP) .…”
Section: Computational Detailsmentioning
confidence: 99%
“…[17][18][19] Its success was demonstrated by determining the stable structures of the various compounds. [20][21][22][23][24] All structural optimizations, calculations of the enthalpies, electronic calculations, and other structural property calculations were performed with the Vienna ab initio simulation package (VASP). [25] The Perdew-Burke-Ernzerhof generalized gradient approximation (GGA) [26] was chosen as the exchange-correlation functional, and projector-augmented wave (PAW) [27] potentials were adopted to describe the ionic potentials.…”
Section: Computational Detailsmentioning
confidence: 99%
“…They found that the inclusion of dispersion, as implemented in Grimme's PBE-D2 functional, did not substantially influence their structural parameters nor their energies, in contrast to the results for elemental sulfur [19]. DFT calculations have concluded that, based upon the energy alone, β-Na 2 S 2 is somewhat more stable than α-Na 2 S 2 [19,20]. Crystal structure prediction (CSP) techniques coupled with DFT calculations have been employed to search for new ambient pressure phases [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of the Na-S battery include the fact that it is made from inexpensive materials, has a long cycle lifetime, and it can deliver high-energy densities [15][16][17][18]. Density functional theory (DFT) calculations [19][20][21] and experiments [20] have been carried out to study the ambient pressure phases with Na 2 S n , n > 1. Momida and co-workers only considered the known phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation